STRATEGI PENGELOLAAN KELAS DI SEKOLAH DASAR - Isnanto Isnanto; Samsi Pomalingo; Meldiana N Harun (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2020)
The Objective of this research was to explore teacher’s role in maximizing the potency of the class; factors inhibiting classroom management; teacher’s efforts in coping with issues of classroom management; and classroom management strategies. This case study was conducted at elementary school of SDN 83 Kota Tengah Gorontalo City, and employed a qualitative approach. The data were collected from technical and source triangulations. The result shows that in classroom management, the teacher serves as a counselor, motivator, facilitator, demonstrator, and evaluator. Therefore, the teacher was able to analyze issues revolving around the students, teachers, as well as the physical and socio-emotional environment in the classroom. Regarding this, the teacher endeavors to apply preventive and corrective acts with the involvement of the school and the committee. Teacher tends to apply eclectic or pluralistic approach in which two or more approaches were applied at the same time. Accordingly, it was expected that the eclectic approach helps teachers improve their capacity in selecting approaches that allow them to cope with problems regarding classroom management